1997
DOI: 10.1099/00221287-143-12-3913
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity of a bacterial community determined from Siberian tundra soil DNA

Abstract: Genomic DNA was isolated from the active layer of tundra soil collected from the Kolyma lowland, Northeast Eurasia, near the Arctic Ocean coast. The SSU (small subunit) rRNA genes were amplified with eubacterial primers from the bulk genomic community DNA and cloned into plasmid vectors. Forty-three SSU rDNA clones were obtained, and all of them had different RFLP patterns. Phylogenetic analysis based on partial sequences (about 300 bp) established with the maximum likelihood method revealed the presence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
1
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(130 citation statements)
references
References 15 publications
4
123
1
2
Order By: Relevance
“…Phylogenetic analyses of permafrost soils indicated that the majority of the clone sequences were 5-15% different from those in the current databases (Zhou et al, 1997). The results presented here enabled identification of one of the unknown genera and gave insight into its physiology and function, which remained unknown for most of the bacteria active in situ.…”
Section: Ecological Aspectsmentioning
confidence: 76%
“…Phylogenetic analyses of permafrost soils indicated that the majority of the clone sequences were 5-15% different from those in the current databases (Zhou et al, 1997). The results presented here enabled identification of one of the unknown genera and gave insight into its physiology and function, which remained unknown for most of the bacteria active in situ.…”
Section: Ecological Aspectsmentioning
confidence: 76%
“…SSU rRNA genes were amplified from genomic DNA using modified primers fD1 and rP1 (Weisberg et al 1991, Zhou et al 1995. Amplification, sequencing, and sequence analysis were performed as previously described (Smith et al 1994, Strunk et al 1996, Zhou et al 1997.…”
Section: Methodsmentioning
confidence: 99%
“…In Siberian tundra soil, it was found that over 60% of the 16S rDNA clones belonged to the Proteobacteria and 16% to the Fibrobacter division (Zhou et al, 1997). It was also found that the soil type was the dominant factor influencing the diversity of the population of culturable fluorescent Pseudomonas spp.…”
Section: The Effect Of Soilmentioning
confidence: 83%